Hubungan Perkembangan Menggambar Bebas dengan Kemampuan Berhitung Anak di Taman Kanak-kanak - Lourena, Dian; Mayar, Farida (Lembaga Yasin AlSys, 2024)
The background of the issue in the study is that cognitive abilities of children are still underdeveloped. Especially in children's arithmetic abilities when doing free drawing activity. This research objective is to see the relationship between the development of free drawing and children's arithmetic abilities. Therefore, the issue that will be examined in this research is